Territorial cohesion, the COVID-19 crisis and the urban paradox: Future challenges in urbanization and economic agglomeration - Artelaris, Panagiotis; Mavrommatis, George (REGION, 2022)
The recent COVID-19 pandemic and the subsequent economic downturn due to the lockdown of economic activities have spurred a lively debate concerning their effects across locations in the EU and the resulting challenges to territorial cohesion policy. The COVID-19 emergency not only has provoked EU cohesion policy responses but also may change some of the basic principles on which these policies have been built. This paper briefly casts light on some present and future implications of the COVID-19 pandemic for two fundamental aspects of territorial cohesion policy, namely urbanization and economic agglomeration. Both aspects are linked to territorial cohesion's significant dimension of polycentricity (as balanced and harmonious development), and together they constitute a challenge to established norms of urban agglomeration. Finally, the paper discusses some policy ideas that have recently (re)appeared on the European policy landscape. Such policy options bring together urban development and regional policy agendas with the aim of promoting territorial cohesion by attempting to solve the `urban paradox' - the coexisting positive and negative effects of urban agglomeration and its established geography.